Design and Build a Goods Demand Forecasting Application using the Simple Averages Method at PT Cahaya Surya Jaya Sentosa - Sugianto, Christananda Manuel; Widana Putra, I Gusti Ngurah Alit; Soebijono, Tony Soebijono S (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2021)
PT Cahaya Surya Jaya Sentosa Demands for goods (sales) is the driving factor of a company. If the company can meet customer demand well, then the company can run well. The company should be able to provide the goods for sale of the next period. PT Cahaya Surya Jaya Sentosa is a distributor of Lang Balm that provides three kinds of balsam, namely 10gram, 20gram, and 40gram. PT Cahaya Surya Jaya Sentosa serves 1500 stores with detail of 225 wholesalers, 450 semi wholesalers (self-service), and 825 retail. With a considerable demand scale, the company has problems in determining the number of products (goods) for the next period of sales. By using System Development Life Cycle (SDLC) method, it is expected to build an application that can predict the demand for goods at PT Cahaya Surya Jaya Sentosa. The algorithm used in forecasting is the simple averages method. Simple averages use a number of new demand actual data to generate forecast values for future requests". This method is effectively applied if it is assumed that market demand data on the product will remain stable at all times. This method has two special properties, namely to make forcasting require historical data in a certain period of time, the longer the moving average will create a smoother moving average. This study used balsam product data in the period January 2015 to July 2020. So the results obtained for the next month are Rp.62.471.022.0 for balsam products 10gram, Rp. 112.705.696.5 for balsam products 20gram, and Rp. 18.889.530.9 for balsam products 40gram.Â Keywords: Balsam, Sales, ForecastingÂ